PENGUATAN MODERASI BERAGAMA DAN HARMONI SOSIAL MELALUI PENDIDIKAN AGAMA ISLAM DI SMPN 12 GRESIK - Angela Eka Rismadianfi; Siti Aisyah; M. Muizzuddin (Journal Multicultural of Islamic Education, 2024)
This study aims to examine the reinforcement of religious moderation through Islamic Religious Education (IRE) and its contribution to fostering students’ social harmony in SMPN 12 Gresik, a multicultural secondary school in Indonesia. Employing a qualitative descriptive approach, the study collected data through in-depth interviews, participant observation, and document analysis involving Islamic Religious Education teachers, students, and school administrators. Data were analyzed using the Miles and Huberman interactive model, encompassing data reduction, data display, and conclusion drawing. The findings reveal that the reinforcement of religious moderation is implemented through the integration of values such as tolerance, respect for diversity, social cooperation, and inclusivity within both classroom learning and the broader school culture. Islamic Religious Education teachers play a pivotal role in cultivating students’ moderate religious attitudes through dialogical pedagogical practices and social role modeling. Furthermore, students’ social harmony is strengthened through open social interactions, an inclusive school environment, and collaborative activities that transcend religious and social differences. The study concludes that Islamic Religious Education serves as a strategic instrument for promoting religious moderation and fostering social cohesion within multicultural educational settings. These findings underscore the importance of integrating inclusive religious values into educational practices to support peaceful coexistence and strengthen intercultural understanding among students.